2005
DOI: 10.1108/00070700510573186
|View full text |Cite
|
Sign up to set email alerts
|

Development of wine from infused tea leaves (Cammellia sinensis)

Abstract: PurposeTea and herb teas are popular beverages with potential health benefits. This study evaluates the potential for the development of wine using infused tea leaves as a raw material.Design/methodology/approachTea leaves of clones 318 and 143 obtained from the Mambilla Highland of the Cocoa Research Institute of Nigeria Ibadan, were infused in hot water and used in wine production. Processed tea bags from Unilever Plc, Nigeria (LP) were used as the control. All the three infusions were fermented for 120 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
(10 reference statements)
2
11
0
Order By: Relevance
“…Similar results were obtained with wines prepared from Indian gooseberry ( E. officinalis ) (Soni et al . 2009), herbal wine from infused tea leaves (Aroyeun et al . 2005) and other tropical fruits such as litchi ( Litchi cinensis Sonn.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were obtained with wines prepared from Indian gooseberry ( E. officinalis ) (Soni et al . 2009), herbal wine from infused tea leaves (Aroyeun et al . 2005) and other tropical fruits such as litchi ( Litchi cinensis Sonn.)…”
Section: Resultsmentioning
confidence: 99%
“…2007). The polyphenol content of a tea wine after 6‐months maturation varied from 0.0013 g/100 mL to 0.0091 g/100 mL depending upon the clone type (Aroyeun et al . 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the taste of the tea beverage compared well with that of grape wines being produced in this laboratory and found as much favour with the tasters. Aroyeum et al 3 also reported good acceptability of the sensory parameters of their tea wine preparation. The tea beverage exhibited a low bitterness, in contrast to what is typical of tea.…”
Section: Sensory Analysismentioning
confidence: 97%
“…Therefore, greater extraction at 100° could have resulted in better fermentation and the resultant lower residual sugars. Aroyeun et al 3 have also reported on experiments with hot water for preparing tea infusions for tea wine production.…”
Section: Preparation Of Tea Infusionmentioning
confidence: 99%